Study of mediation effect of affinity in defining relationship between social media and career decisions of Gen-Z - Bhore, Milind; Tapas, Poornima (Zielona Góra: Faculty of Economics and Management Press)
Gen-Z leverage social media to showcase their skills and talent to ensure good career opportunities. The objective of this research is to study the mediation effect of affinity towards social media in defining relationship between social media and career decisions made by Gen-Z. Purposive sampling technique is used to collect responses from 500 Gen-Z.
Keywords: Gen-Z; social media; affinity; career decisions; mediation effect